Macro element and dynamic seismic analysis of the medieval government building of Perugia, Italy. (30th May 2019) - Castori, Giulio; Corradi, Marco; Borri, Antonio; Sisti, Romina; Maria, Alessandro De
This paper emphasises the actual structural analysis of a multistory medieval building, located in Perugia, Italy, for seismic resistance. This is the local governor building of the capital city of Umbria, known as Palazzo dei Priori, an iconic grade-I stone masonry construction. Strong emphasis is placed on specific issues, critical for the structural response of the building under the seismic action. Fundamental assessment methods are presented and discussed to find vulnerabilities and defects that affect its seismic response. The discussion includes the analysis by macro-elements (local analysis), leading to the identification to the most likely collapse mechanisms of the building under the seismic action. In addition to the macro-element method, a nonlinear analysis is given for the whole building. All the used analyses are carried out with reference to the Italian guidelines for heritage protection and conservation and by considering the architectural and artistic assets of the building.